Myxoid liposarcoma: it's a hippo's world - Carla Regina; Simone Hettmer (EMBO Molecular Medicine)
Abstract Fused in sarcoma: DNA damage‐inducible transcript 3 protein (FUS:DDIT3) is a chimeric fusion oncoprotein present in 90% of human myxoid liposarcomas (MLS). The study by Trautmann et al in this issue of EMBO Molecular Medicine utilizes a drop‐out RNAi screen to establish hyperactive Yes‐associated protein 1 (YAP1), a major downstream nuclear effector of the Hippo signaling pathway, as a selectively essential transcript promoting viability and growth of MLS. These observations add to a growing body of evidence underscoring the importance of dysregulation of Hippo signaling in soft‐tissue sarcomas expressing fusion oncoproteins and identify a novel target for therapeutic intervention in MLS. Comprehensive molecular characterization pipelines are needed to screen patients with advanced soft‐tissue sarcomas for the presence of druggable alterations, including but not limited to nuclear YAP1 expression in MLS, to facilitate treatment decisions and advance therapy.